The performance and durability of high-temperature proton exchange membrane fuel cells enhanced by single-layer graphene. (March 2022) - Chen, Jianuo; Bailey, Josh J.; Britnell, Liam; Perez-Page, Maria; Sahoo, Madhumita; Zhang, Zhe; Strudwick, Andrew; Hack, Jennifer; Guo, Zunmin; Ji, Zhaoqi; Martin, Philip; Brett, Dan J.L.; et al.
Abstract: Single-layer graphene (SLG) obtained by chemical vapor deposition is applied between membrane and electrodes by a wet chemical transfer method to study its effect on the performance and durability of polybenzimidazole membranes in high-temperature proton exchange membrane fuel cells (HT-PEMFCs). After accelerated stress testing (AST), the membrane electrode assembly (MEA) loaded with SLG at different positions exhibits higher peak power density, lower electrode resistances, and larger electrochemical active surface area than pure polybenzimidazole membranes with high phosphoric acid doping level. The peak power density of the MEAs with both cathode and anode loaded with SLG is 480 mW cm -2 after AST, while those based on pure membranes is 249 mW cm -2 . Lab-based X-ray micro-computed tomography combined with Raman spectroscopic mapping was applied for the first time to study the effect of SLG on controlling phosphoric acid leaching. In addition, samples containing SLG on an ultra-thin membrane (7.5 µm) were also tested to explore its influence on hydrogen crossover. After 100 h of galvanostatic discharging, the hydrogen crossover of samples loaded with single-layer graphene on the anode does not exceed 1.75 × 10 −4 mol s -1, which is much lower than that of MEAs made using pure ultra-thin membranes (8.16 ×10 −4 mol s -1 ). Graphical Abstract: This work applies high-quality single-layer graphene to a high-temperature proton exchange membrane fuel cell. Through electrochemical characterization, X-ray micro-computed tomography and Raman spectroscopic mapping, this work proposes a mechanism for monolayer graphene to improve the performance and durability of high-temperature fuel cell by controlling its phosphoric acid leaching and hydrogen crossover. ga1 Highlights: Single-layer graphene (SLG) prepared by CVD was first applied in PEMFC. Large-size and high-quality SLG was transferred on electrodes with certain coverage. New mechanism was proposed to control phosphoric acid leaching and H2 crossover. New mechanism was proposed to maintain the shape of three-phase boundary in HT-PEMFC. X-ray CT and Raman mapping was combined to study the phosphoric acid leaching.